SPE Oil and Gas India Conference and Exhibition 2010
DOI: 10.2118/129012-ms
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of Low Salinity Waterflooding as Secondary Recovery Process: Effect of Wettability

Abstract: Laboratory studies along with field tests conducted over the decade reveal that reducing the salinity of water injected into reservoirs improves the oil recovery. Different phenomena e.g. increase in pH (alkalinity), fines migration, multi-component ionic exchange, etc., have been proposed by researchers for improved oil recovery during low salinity waterflooding (LSW). Though LSW has attracted attention among reservoir engineers as tertiary recovery process, limited studies have reported the potential of LSW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 13 publications
2
46
1
Order By: Relevance
“…Low-salinity water (LSW) flooding has been widely documented as a promising improved oil recovery technique in literature (Ashraf et al, 2010;Morrow and Buckley, 2011;Morrow, 1997, 1999). In this process, the brine chemistry has been recognized as an important parameter critically affecting the efficiency of the process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-salinity water (LSW) flooding has been widely documented as a promising improved oil recovery technique in literature (Ashraf et al, 2010;Morrow and Buckley, 2011;Morrow, 1997, 1999). In this process, the brine chemistry has been recognized as an important parameter critically affecting the efficiency of the process.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, the brine chemistry has been recognized as an important parameter critically affecting the efficiency of the process. Different laboratory and field studies have proved the remarkable low salinity effect on the ultimate oil recovery and reported greater oil recovery with decreasing the ionic strength of water (Ashraf et al, 2010;Hassenkam et al, 2012). On the other hand, the brine chemistry drastically affects the interactions of colloidal particles, situated on the pore walls, with the medium surface (Lager et al, 2008;Nasralla et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Fogden and Lebedeva (2011) found out that there was increased oil particles deposited on kaolinite surfaces in low salinity environment than in high salinity water environment. Ashraf et al (2010) carried out secondary corefloods with oil having different wetting tendencies and reported that low salinity water improved recovery under oil wet, water wet and neutral wet conditions, with the water wet conditions showing the biggest low salinity water effect. Positive low salinity effect was also seen in tertiary corefloods using both predominantly basic oil and a predominantly acidic oil .…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers reported that low salinity water flooding change the wettability into neutral state rather than water-wet state [8], [9]. Ashraf et al [4] pointed out same result.…”
Section: Wettability Effects and Its Alterationmentioning
confidence: 84%
“…The performance of a water flooding is typically affected by the following main parameters: reservoir geology and geometry, physical properties, porosity, permeability, heterogeneity, fluid properties: viscosity, mobility ratio, mineralogical properties: clay type and amount. Over decades much research has been done to optimize these parameters to be able improve water flooding process [4]. The effect of water chemistry on brine-rock interactions was seldom paid any attention, even though the effect of low salinity brine in sandstone rock containing clay was revealed in the 60's.…”
Section: Introductionmentioning
confidence: 99%